Simple Meets Single: The Application of CRISPR/Cas9 in Haploid Embryonic Stem Cells. (3rd October 2017) - Yin, Zixi; Chen, Lingyi
Abstract : The CRISPR/Cas9 system provides a powerful method for the genetic manipulation of the mammalian genome, allowing knockout of individual genes as well as the generation of genome-wide knockout cell libraries for genetic screening. However, the diploid status of most mammalian cells restricts the application of CRISPR/Cas9 in genetic screening. Mammalian haploid embryonic stem cells (haESCs) have only one set of chromosomes per cell, avoiding the issue of heterozygous recessive mutations in diploid cells. Thus, the combination of haESCs and CRISPR/Cas9 facilitates the generation of genome-wide knockout cell libraries for genetic screening. Here, we review recent progress in CRISPR/Cas9 and haPSCs and discuss their applications in genetic screening.